HUBUNGAN ANTARA PLAYFULNESS DAN PSYCHOLOGICAL WELL-BEING PADA GENERASI X DAN Z - Larasati, Ajeng Meilyana; Rahma Hastuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate the relationship between playfulness and psychological well-being across two generational groups, namely Generation X and Generation Z. The participants consisted of 220 individuals, comprising Generation X (n = 104; aged 43–58) and Generation Z (n = 116; aged 18–25). Data were collected online using the Short Measure of Adult Playfulness (SMAP), the OLIW Model of Adult Playfulness, and the Psychological Well-Being Scale. Data analysis was conducted using Spearman correlation and additional mean difference tests based on gender and age. The results show a significant positive relationship between playfulness and psychological well-being in both Generation X (r = 0.922; p < 0.001) and Generation Z (r = 0.697; p < 0.001). These findings indicate that higher levels of playfulness are associated with higher levels of psychological well-being across both generations. Additional analyses revealed significant gender differences in playfulness and psychological well-being in Generation X, whereas no gender differences were found in Generation Z. Furthermore, no age-based differences were found for either variable in both generational groups. Overall, this study highlights playfulness as an important psychological resource that contributes to psychological well-being across generations. The findings are expected to serve as a reference for future interventions and research in the field of positive psychology.